New data on Empis Linnaeus (Diptera: Empididae) from Iran, with description of a new species of the subgenus Lissempis Bezzi - Kazerani, Farzaneh; Khaghaninia, Samad; Talebi, Ali Asghar; Shamshev, Igor (Zootaxa, 2014)
Fourteen species of the genus Empis Linnaeus were collected and identified from Iran. Empis (Lisssempis) guilanensis Kazerani & Shamshev sp. nov. is described and illustrated from Guilan province in north central Iran. The following seven species were recorded from Iran for the first time: E. (Euempis) tessellata Fabricius, 1794; E. (Pachymeria) mediterranea (Loew, 1864); E. (P.) obscuripes (Loew, 1873); E. (Polyblepharis) dedecor Loew, 1869; E. (P.) engeli Chvála, 1999; E. (P.) soror Collin, 1937; E. (P.) spirifera Bezzi, 1909. An identification key to the subgenera and species of Empis from Iran are provided.